2009
DOI: 10.1093/humrep/dep058
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin in cisplatin-induced oxidative injury in rat testis: mitogen-activated protein kinase and nuclear factor-kappa B signaling pathways

Abstract: MAPK and NF-kB activation have a significant role in CIS-induced testicular toxicity. CMN has a strong potential for use as a therapeutic adjuvant in CIS gonadotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
149
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 58 publications
29
149
0
1
Order By: Relevance
“…The protective effect of curcumin on induced tissue damage due to free radicals has been observed previously in a number of experimental models. [14][15][16][17] Previous studies have demonstrated that curcumin also exhibits an antioxidant property as well as anti-inflammatory, immunomodulatory, anticancer, and antiangiogenic properties via its pleiotropic effects on genes and cell-signaling pathways at multiple levels. [18] A recent experimental SCI study showed that curcumin blocked apoptosis and neuron loss, restrained astrocyte activation, and significantly improved neurologic deficit.…”
Section: Resultsmentioning
confidence: 99%
“…The protective effect of curcumin on induced tissue damage due to free radicals has been observed previously in a number of experimental models. [14][15][16][17] Previous studies have demonstrated that curcumin also exhibits an antioxidant property as well as anti-inflammatory, immunomodulatory, anticancer, and antiangiogenic properties via its pleiotropic effects on genes and cell-signaling pathways at multiple levels. [18] A recent experimental SCI study showed that curcumin blocked apoptosis and neuron loss, restrained astrocyte activation, and significantly improved neurologic deficit.…”
Section: Resultsmentioning
confidence: 99%
“…The biochemical results of these workers have shown the generation of free radicals in each case as they demonstrated that cisplatin treatment was characterized by a significant increase in tissue malon-dialdehyde level compared to normal control (Ilbey et al, 2009). This study investigated the associated response of neural and other parameters in response to cisplatin toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Th e eff ects of the curcumin on inducible nitric oxide synthase (iNOS) expression, nuclear factor-kappa B (NF-kB) activation, and MAPK in the pathogenesis of testicular damage induced by cisplatin (CIS) have been investigated (Ilbey et al 2009). Curcumin (200 mg/kg, p.o.)…”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 99%
“…Curcumin (200 mg/kg, p.o.) increased plasma testosterone levels, GSH levels, and glutathione peroxidase (GSH-Px) activity and decreased MDA and NO levels in the testicular tissue compared with the CIS-induced toxicity group (Ilbey et al 2009).…”
Section: Th E Eff Ect Of C Longa and Curcumin On Male Reproductive Smentioning
confidence: 99%